Development of surface plasmon resonance based assay for simultaneous detection of Hepatitis C and B viral infections - Akhavanrezaei, Morvarid (2015)
Hepatitis C (HCV) and Hepatitis B virus (HBV) infections are major public health issue worldwide. These two hepatotropic viruses share same ways of transmission and also coinfection with these two viruses is not unusual, especially in areas with a high prevalence of HBV infection and among people at high risk for parenteral infection (Liu and Hou 2006). It is imperative that effective and reliable techniques for hepatitis C virus (HCV) and hepatitis B (HBV) infection diagnosis be devised. Additionally, non-reactive and misdiagnosis, often demanding iteration of tests for confirmation. Biosensors based on surface plasmon resonance (SPR) detection assay provides a solution for these limitations. Additionally, the SPR can overcome the contamination susceptibility of molecular methods that rely heavily on the purity of the template nucleic acid and that would result in false positives. This study proposes an optimized SPR protocol for large-scale Hepatitis C and B samples screening. HCV and HBV detection chips were set up separately. The HCV detection chip was established by immobilization of HCV Core genotype 1, HCV Core genotype 3a and HCV NS5 genotype 3a antigens for hepatitis C genotype screening. On the other hand, HBs Ag and HBsAg antibody were used to establish the HBV screening chip. The limit of detection (LOD) was calculated for each immobilized flow cell of each established chip used 20 human donor serums were each spiked with HCV antibody for HCV established chip and 20 human donor serums were each spiked with HBsAg antibody for HBV established chip. LOD of HCV detection chip was in the range of 14.4 – 33.48 pg/ ml followed by a range of 18- 25.2 pg/ml for HBV detection chip used . A total 137 HCV positive and negative samples were collected. All of the 137 tested as positive or negative HCV samples, were analyzed for genotype 1 and genotype 3a with established HCV screening chip. 37 samples were tested positive for HCV antibody, showed 100% positivity for genotype 1. Consequently, 6.6 % tested positive for core genotype 3a, while 16% tested positive for NS5 genotype 3a.Among the genotype 3a samples tested positive, only one sample showed positive results for both core 3a and NS5 3a. A total 400 HBV positive and negative samples were collected. All 100 positive HBsAg, 100 negative HBsAg and 200 negative HBsAg antibody samples were confirmed serologically by the HBV established chips. Finally, the HBsAg, HCV core genotype 1 and HBsAg antibody were immobilized to establish the dual detection chip. Based on the international distribution of HCV genotype 1, it was chosen to establish the dual detection chip. The LOD for this dual detection chip was in the range of 12.6–26.4 pg/ml. To determine the LOD for this established chip, 20 human donor serums were used and each sample spiked with HCV antibody and HBsAg antibody individualy and analysed with established chip. Out of total 137 samples, 37 samples tested positive for HCV antibody and 100 tested negative for HCV antibody. Among oof 400 samples, 100 samples tested positive for HBsAg, 100 samples tested negative for HBsAg and 200 samples tested HBsAg antibody negative. A comparison was made between the SPR and ELISA techniques in the diagnosis of HCV and HBV infection. It was found that there was a strong correlation between SPR and ELISA test when used to detect HCV and HBV in the samples. The correlation coefficient obtained with the two techniques approached 1 (P< 0.01). The range of linear dose was observed for each immobilized flow cell with a coefficient of determination between 98 to 99%. The novelty of this study is the ability to serologically detect HCV and HBV antigens and antibody, as well as HCV genotypes mixture simultaneously. LOD for developed SPR chips (observed between 14.4 – 33.48 pg/ml) showed higher efficiency when compared to HCV and HBV commercially used enzyme-linked immunosorbent assay (ELISA) and chemiluminescent immunoassay (ChLIA) (ng/ml). Due to the low detection limit of SPR compared to ELISA and ChLIA, it can detect false negative samples caused by lower level of antibody and antigen than ELISA and ChLIA detection limit, a greater efficiency lacking in the later mentioned application. In conclusion, the optimized SPR approach can serve as a standard operating procedure (SOP) for national blood screening centers. Taken together, data indicate that the assays developed are highly reproducible, specific and sensitive , accuracy, precision, repeatability, linearity, range and robustness.. This biosensor-based assay is a more efficient tool for accurate screening of antibody and antigen in HCV and HBV infected patient serum, while retaining the advantages of ELISA. Moreover, the inbuilt robotic automated system with reusable chip is on the top of novelty for this dual antigen and antibody detection assay for suspected co-infected samples.